Dimensão psicossocial e dificuldades diárias relacionadas ao diabetes: concordância entre médicos e pacientes - Roberta Carvalho de Figueiredo (2013)
Physician-patient relationship is a crucial element of effective diabetes care. However, effective communication is complex because professionals and patients perspectives may differ. This thesis, presented by way of four articles, looked into the difficulties for patients diabetes care and explored the differences between patients and their own physicians perceptions about diabetes-specific issues. This thesis using a mixed methods approach integrating qualitative and quantitative methods. First, we conducted two focus groups meetings with patients with diabetes who attended primary and secondary health services in the city of Belo Horizonte Minas Gerais. The number of participants ranged from four to seven, two females and five males. The analytical strategy is rooted in the Grounded Theory. Second, we developed a cross-sectional epidemiological study among patients with diabetes and their own Family Health physicians who attended 108 primary healthcare centres distributed in nine Health Districts in Belo Horizonte, Brazil. 282 patient-physician pairs were included and interviewed face-to-face using standard questionnaires. After studying the group discussions, five themes emerged from the analysis regarding participants perceptions: "Diabetes: shock, anger, sadness," "emotional state and diabetes: cause and effect, managing diabetes: a sacrifice, "diet: the greatest dilemma" and "insulin: signs, symptoms and fears". It was possible to grasp a bidirectional relationship between emotional disorders and diabetes. Follow the prescribed diet is the most challenging aspect of diabetes care and we see great dissatisfaction with the use of insulin, mainly by associating its use with the worsening of the disease and with hypoglycemia. The participants struggle to integrate self-care activities in their everyday life. How they react to this integration process varies according to their psychological barriers. The data from cross-sectional study allowed us to explore the perceptions of patients with diabetes and their physicians about the diabetes care, their differences their explanatory models. The fact that 20% of the pairs disagree was worrying as we would expect that almost all pairs agreed on this important and very objective issue. We noticed that the information given by physicians is generally poorly apprehended by their patients, especially by less educated patients. Recognizing that diabetes-related distress seems to be a problem among Brazilian diabetic patients, the third article aimed to validate the Brazilian version of the PAID-5 (B-PAID-5). Our findings suggest that the B-PAID-5 possesses good reliability and validity. In addition, the results support the hypothesis that physicians' perceptions of patients are influenced by patients' race and socio-economic status. Physicians rate black patients and those who live at neighbourhoods with high risk Health Vulnerability Index as having higher distressed. Physicians and other health professionals should avoid making assumptions about a patients understanding of diabetes or that they correctly understand their instructions and advices. Educational programmes need to develop comprehensible and effective strategies to guarantee that health information will reach the most socially vulnerable groups of the population.